A study in development : institutional aspects of economic growth and social development - Vermeulen, Adrianus; Sanders, C. (Rotterdam, Rotterdam University Press, 1970)
This book examines the institutional aspects of economic growth and social development with topics like: the role of the state; trade unions; trade and employers organisations; a modern approach to industrial relations; industrial productivity agencies.
Includes bibliographical references.
lje 19/09/2018
Loans
Keywords: Economic development; Social development; Economic growth